Single-Cell Tracking of A549 Lung Cancer Cells Exposed to a Marine Toxin Reveals Correlations in Pedigree Tree Profiles - Korsnes, Mónica Suárez; Korsnes, Reinert (Frontiers in Oncology, 2018)
Long-term video-based tracking of single A549 lung cancer cells exposed to three different concentrations of the marine toxin yessotoxin (YTX) reveals significant variation in cytotoxicity, and it confirms the potential genotoxic effects of this toxin. Tracking of single cells subject to various toxic exposure, constitutes a conceptually simple approach to elucidate lineage correlations and sub-populations which are masked in cell bulk analyses. The toxic exposure can here be considered as probing a cell population for properties and change which may include long-term adaptation to treatments. Ranking of pedigree trees according to a measure of ''size'', provides definition of sub-populations. Following single cells through generations indicates that signalling cascades and experience of mother cells can pass to their descendants. Epigenetic factors and signalling downstream lineages may enhance differences between cells and partly explain observed heterogeneity in a population. Signalling downstream lineages can potentially link a variety of observations of cells making resulting data more suitable for computerised treatment. YTX exposure of A549 cells tend to cause two main visually distinguishable classes of cell death modalities ("apoptotic-like" and "necrotic-like") with approximately equal frequency. This special property of YTX enables estimation of correlation between cell death modalities for sister cells indicating impact downstream lineages. Hence, cellular responses and adaptation to treatments might be better described in terms of effects on pedigree trees rather than considering cells as independent entities.